Conciencias Lingüísticas y el desarrollo del lenguaje oral en los niños de 4 a 5 años - Chuqui Saquinga, Lourdes Conzuelo (2022)
This research study was carried out with the purpose of diagnosing the importance of Linguistic Awareness and its application in Early Childhood Education at "Pujilí" Educational Unit. In addition, its influence on the oral language development of children from 4 to 5 years old. The problem was generated by the lack of information and application that teachers have about them to be executed correctly in the development of the oral language of infants, on the other hand, the lack of family support has prevented the participation of children in an active way. In order to carry out this research, relevant literature and bibliographic review were conducted within the educational field with the aim of identifying oral language problems, through the application of interviews and observation forms, to develop Linguistic Awareness by reinforcing pre-reading and pre-writing in children, which allowed understanding the definition, characteristics, and importance of the application in the Initial 2 sub-level in educational institutions. For the development of this research, the qualitative approach was used with the use of the inductive method that helped to clearly and precisely detail the characteristics and processes of oral language development. In the same way, the application of the interview technique to the teachers and the observation form to the children allowed the collection of information and data, which helped to support the research carried out. The research was used to establish the diagnosis of the problem and final conclusions, mentioning that most teachers occasionally apply lexical, semantic, syntactic, and phonological awareness, which has limited the development of the oral language of the students. Finally, this research had a great educational impact, since it is aimed at improving children's language development, considering that at this educational level the basic and necessary knowledge is provided for the initiation to pre-reading and pre-writing through the application of the same, so it depends to a great extent on the intervention of the teacher and the family in the progress of oral language in the early stage.